2008
DOI: 10.1007/s00705-008-0057-2
|View full text |Cite|
|
Sign up to set email alerts
|

HN protein of Newcastle disease virus causes apoptosis in chicken embryo fibroblast cells

Abstract: Newcastle disease virus (NDV), an avian paramyxovirus, induces apoptosis in chicken embryo fibroblast (CEF) cells. In the present investigation, the ability of haemagglutinin-neuraminidase (HN) protein of NDV to cause apoptosis in CEF cells was examined. The results revealed that cells expressing the HN protein demonstrated decreased DNA content, phosphatidylserine exposure and increased cytoplasmic vacuolation. Up-regulation of caspase-1, -9, -8, -3, loss of mitochondrial transmembrane potential and an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
3
35
0
1
Order By: Relevance
“…(2). In recent years, although some aspects of NDV pathogenesis have been investigated, the factors that affect NDV replication in its host are still poorly understood (3)(4)(5).…”
mentioning
confidence: 99%
“…(2). In recent years, although some aspects of NDV pathogenesis have been investigated, the factors that affect NDV replication in its host are still poorly understood (3)(4)(5).…”
mentioning
confidence: 99%
“…In our previous studies, we showed that the HN protein can cause apoptosis in chicken embryo fibroblasts and in HeLa cells [14,21]. We have demonstrated the activation of the SAPK/JNK pathway by HN [13].…”
Section: Discussionmentioning
confidence: 92%
“…The results showed a significant decrease in mitochondrial membrane potential in HN ? TNF-a-transfected HeLa cells at 48 h p.t., confirming the loss of mitochondrial membrane potential, which is an upstream event occurring during the mitochondrial pathway of apoptosis [14]. The loss of mitochondrial membrane potential leads to an efflux of cytochrome-c from the intermembrane space of mitochondria to the cytoplasm and initiates formation of the apoptosome, resulting in the proteolytic activation of the initiator caspase-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of apoptosis by NDV requires viral entry, replication, de-novo protein synthesis, and activation of caspases. In addition to its direct cytopathic effects, the anti-cancer activity of NDV is associated with the activation of both innate and adaptive immune responses [51].…”
Section: Newcastle Disease Virus (Ndv)mentioning
confidence: 99%